The Effect of Beta, and Residual Income on Stock Return in The Manufacturing Industry in The Indonesia Stock Exchange - Muhamad Syafril Nasution; Almira Keumala Ulfah; Trie Nadilla; Ramadhan Razali; Husni Kamal; Supriyanto Supriyanto (Institute of Computer Science (IOCS), 2021)
This study intends to re-examine the factors that affect the level of stock returns. In this study, the factors studied are beta and residual income, and the level of stock return is indicated by the closing price. This study is a replication of Pradhono's research which examines the effect of Economic Value Added, Residual Income, Earnings, and Operating Cash Flows on the return received by shareholders. In this study, there are several differences from previous research.This study uses another variable, namely beta which is measured by point estimation using historical data and subjective estimates. The results of this study are partially beta variable has a significant influence on stock returns. Based on the partial test results, the residual income variable does not have a significant effect on stock returns. Simultaneous test results show that residual income and beta have a significant effect on stock returns in manufacturing companies listed on the Indonesia Stock Exchange (IDX). Thus the results of this calculation can be taken as a decision that accepts the hypothesis, meaning that Beta and residual income simultaneously have a significant effect on stock returns in manufacturing companies listed on the Indonesia Stock Exchange (IDX)